Confessions of an Unrepentant Generalist: An Interview With Douglas Lochhead - Boone, Laurel (Studies in Canadian Literature, 1988)
Douglas Lochhead laments the lack of attention paid to Maritime writers. He speaks of his work organizing libraries at Cornell, Dalhousie, and York Universities. He had an instrumental part in organizing the League of Canadian Poets, along with Raymond Souster, Al Purdy, and other poets of note. His own poetry is personal and highly condensed, and is influenced more by modernist American poets than by Canadians. He feels that the twentieth century is better interpreted through the long poem than through the short poem.